Diets for grow-out of pirarucu in net cage: Performance, physiological parameters, fillet composition and feeding cost - Medeiros, Paulo Adelino de; Costa, Edimar Lopes da; Brasil, Elenice Martins; Ono, Eduardo Akifumi; Affonso, Elizabeth Gusmão (Boletim do Instituto de Pesca, 2019)
The present study evaluated practical diets with increasing levels of protein and energy on performance, fillet composition, feed cost, and physiological responses of pirarucu (Arapaima gigas) juveniles during the grow-out phase in a net cage system. In an on-farm trial for 90 days 225 pirarucu juveniles with initial weight ± standard deviation of 2025 ± 335 g were fed to apparent satiety with extruded diets containing 37.4 (T-37), 40.8 (T-40), 43.9 (T-43), 45.5 (T-46), and 47.1% (T-49) crude protein (CP), increasing lipid levels, and energy:protein ratio fixed in 10 kcal g-1. Protein and lipid concentrations in the diets influenced the cost, fillet composition, and important physiological aspects of the health maintenance and productive performance of the pirarucu juveniles. Fish fed the T-37 diet had lower concentrations of fat in body cavity, fillet and blood, and had a lower cost associated with feeding. The increase in protein and energy levels in the other diets tested reduced the economic return, did not improve the zootechnical performance and caused physiological changes in the fish. © 2019, Instytut Technologii Drewna. All rights reserved.
Dietas para a engorda de pirarucu em tanque rede: Desempenho, parâmetros fisiológicos, composição do filé e custos da alimentação